ANALISIS ASPEK ERGONOMI PADA LINGKUNGAN KERJA (STUDI KASUS PADA UNIT PRODUKSI COCO FIBER) - Ida Bagus Suryaningrat; Soni Sisbudi Harsono; Surya Cahyadi (Faculty of Agricultural Technology, University of Jember, 2011)
Temperature, noise and lighting are the most problems faced by industries, especially at the Coco fiber production company. The objectives of this research were to evaluate the working environment factors such as temperature, noise, and lighting. This research was conducted at the Coco fiber production company namely CV Tiga Sehati at Ledokombo, Jember. Questionnaire was addressed to the workers in the processing area of company to get comments related to the working area. Discussion with key person was also implemented in this research to reach data. Direct measurement of working area environment was conducted using several tools such as thermometer, luxmeter and sound level meter. The average of temperature, humidity, noise and lighting were achieved at the level of 29.5oC, 62.9%, 88.9 dB and310.26 lux, respectively. Almost all of these results were higher than standard level. Some of working area improvement were strongly needed to keep safe, health and convenient of the workers.Keywords: ergonomic, work environment, coco fiber